A NOVEL QOS SCHEDULING FOR WIRELESS BROADBAND NETWORKS - D. David Neels Pon Kumar; K. Murugesan; S.Raghavan (ICTACT Journal on Communication Technology, 2010)
During the last few years, users all over the world have become more and more familiar to the availability of broadband access. When users want broadband Internet service, they are generally restricted to a DSL (Digital Subscribers Line), or cable-modem-based connection. Proponents are advocating worldwide interoperability for microwave access (WiMAX), a technology based on an evolving standard for point-to multipoint wireless networking. Scheduling algorithms that support Quality of Service (QoS) differentiation and guarantees for wireless data networks are crucial to the deployment of broadband wireless networks. The performance affecting parameters like fairness, bandwidth allocation, throughput, latency are studied and found out that none of the conventional algorithms perform effectively for both fairness and bandwidth allocation simultaneously. Hence it is absolutely essential for an efficient scheduling algorithm with a better trade off for these two parameters. So we are proposing a novel Scheduling Algorithm using Fuzzy logic and Artificial neural networks that addresses these aspects simultaneously. The initial results show that a fair amount of fairness is attained while keeping the priority intact. Results also show that maximum channel utilization is achieved with a negligible increment in processing time.